Sex differences in relation patterns between health-related quality of life of older adults and its correlates: a population-based cross-sectional study in Madeira, Portugal: Cite this article: Gouveia BR, Ihle A, Kliegel M, Freitas DL, Gouveia ÉR. (2018) Sex differences in relation patterns between health-related quality of life of older adults and its correlates: a population-based cross-sectional study in Madeira, Portugal. Primary Health Care Research & Development page 1 of 5. doi: 10.1017/S1463423618000233. (2019) - Gouveia, Bruna R.; Ihle, Andreas; Kliegel, Matthias; Freitas, Duarte L.; Gouveia, Élvio R.
Abstract: A population-based cross-sectional study aimed to examine sex differences in health-related quality of life (HRQoL) of older adults, and investigate whether the relation patterns between HRQoL and its correlates differed between sexes. A stratified proportional and representative sample included 802 volunteers, aged 60–79. HRQoL (36-item Short Form Health Survey), functional fitness (Senior Fitness Test), physical activity (PA) (Baecke questionnaire), demographic information and health features (questionnaires) were assessed. Men showed significantly higher HRQoL ( P <0.001). Body mass index, body strength, aerobic endurance, PA, depressive symptoms, falls, and living alone were significantly related to HRQoL. With sex as moderator, these relations were not significant, except for PA ( β =0.12, P =0.004). A significant interaction of sex with PA on HRQoL ( β =0.08, P =0.037) was found, indicating that this relation was higher in men. A similar relation pattern was found for HRQoL physical component. HRQoL and its correlates differed between sexes, demanding a sex specific approach to promote HRQoL.